2012
DOI: 10.1177/0004867412464717
|View full text |Cite
|
Sign up to set email alerts
|

The nocebo effect: A clinicians guide

Abstract: The nocebo effect is a common, clinically significant, yet covert driver of clinical outcomes. Increased awareness of its features, as well as knowledge of strategies on how to manage it, are fundamental so that clinicians can mitigate its impact on clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 57 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…For example: health-care interventions can sometimes result in idiosyncratic, unexpected adverse effects in individual patients [27]; sham pills used as 'controls' in RCTs often cause adverse side-effects [28]; and population-based interventions, such as the introduction of mobile phones or wind farms, can result in widespread, unexplained illness [29,30]. These are examples of what have been called 'adverse outcomes resulting from negative expectations' [31] because most investigators have assumed that expectations are responsible for the effects observed.…”
Section: Nocebo Effects and Painmentioning
confidence: 99%
“…For example: health-care interventions can sometimes result in idiosyncratic, unexpected adverse effects in individual patients [27]; sham pills used as 'controls' in RCTs often cause adverse side-effects [28]; and population-based interventions, such as the introduction of mobile phones or wind farms, can result in widespread, unexplained illness [29,30]. These are examples of what have been called 'adverse outcomes resulting from negative expectations' [31] because most investigators have assumed that expectations are responsible for the effects observed.…”
Section: Nocebo Effects and Painmentioning
confidence: 99%
“…Administering an essentially inert substance to a patient or a study participant can influence clinical outcomes such as symptom severity, including improvement or worsening, and may elicit treatment‐emergent adverse events(TEAEs). These phenomena, known as the placebo (improvement) or nocebo (worsening or adverse events) effects, occur commonly and are of varying intensity, are challenging to predict, and may be difficult or impossible to distinguish from the natural progression of some illnesses or naturally occurring adverse events . This concept has been extended to include not only inert substances, but also non‐inert or pharmacologically active substances that are not considered to be effective for the index symptoms being treated …”
Section: Introductionmentioning
confidence: 99%
“…v) Illness investment and abnormal illness behaviour drive somatization and mood symptoms (27,28). Somatization is often seen as an alternative mode for the expression of distress and can manifest as expectation of harm secondary to medical intervention-the nocebo effect (29).…”
Section: Introductionmentioning
confidence: 99%